EFFORT TO INCREASE THE LEARNING INTEREST OF PRIMARY SCHOOL CLASS II STUDENTS IN THE SUBJECT OF OPERATIONS OF ADDITION AND SUBTRACTION THROUGH A DIGITAL FINE PULL EDUCATION GAME - Mawardi; Sikha Fauziah; Nurul Aini; Intan Ayu Fitriani; Rahma Adelia Ramadhani (Journal Informatic, Education and Management (JIEM), 2026)
This research aims to increase the learning interest of students in class II of Primary School on the operation material of addition and subtraction through the use of the Educational Game Tarik Tambang Digital. This research is a Classroom Action Research (Class Action Research) that is carried out in two cycles, with each cycle consisting of planning, action implementation, observation, and reflection. The subjects of the research are students in class II of the Basic School. Data collection techniques are done through observation of teacher actions, observation of student activities, and observation of students' interest in learning during the learning process. The results of the research show that the application of the Digital Mining Educational Game is able to improve the quality of learning. This is shown by the increase in the implementation of the teacher's actions from 85% in Cycle I to 100% in Cycle II, as well as the increase in student activity from 69% in Cycle I to 93% in Cycle II. In addition, students show higher enthusiasm, attention, participation, and involvement during learning. Thus, the use of the Digital Mining Educational Game can be an effective learning media alternative to increase students' interest in learning about addition and subtraction arithmetic operations in class II of Primary School.